PETROPHYSICAL PARAMETERS OF NEAR-SURFACE SANDSHALE ROCKS BASED ON RADIOACTIVE LOGGINGS - Bondarenko, M.; Кulyk, V.; Yevstakhevych, Z. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The apparatus-methodical complex of radioactive logging (AMC RL) for determining set of petrophysical parameters of near-surface sandshale rocks is developed. AMC RL includes gamma-ray logging (GL), neutron-neutron logging (NNL), gamma-gamma logging (GGL); radioactive logging apparatus; interpretating-methodical support and software. In the general case, petrophysical parameters of rocks can be determined by combining the measured parameters of the radioactive logging with the use of a number of a priori data. AMC RL allows to determine: parameters of density, shaliness, porosity, volume moisture content, groundwater level, etc. A number of new techniques for determining these parameters by nuclear geophysical methods are proposed. The features of obtaining parameters in the zone of full water saturation and in the aeration zone are shown. A number of parameters were first determined using geophysical well logging. A set of two-channel tools 2NNL and GGL+GL as well as a three-component tool 2NNL+GGL+GL, which meet modern requirements, have been developed, produced and tested. Efficiency of the developed approaches and tools is demonstrated by the example of determination of petrophysical parameters in cased well.
Keywords: near-surface rocks; petrophysical parameters; combination of gamma-ray logging; neutron-neutron logging and gammagamma logging; radioactive logging apparatus; shaliness; density; porosity; volume moisture content; water saturation